2021
DOI: 10.51470/plantarchives.2021.v21.no1.114
|View full text |Cite
|
Sign up to set email alerts
|

Palynological Investigations on Some Selected Bee Forage Plants of Family Fabaceae Using Light and Scanning Electron Microscopy From Himachal Pradesh, India

Abstract: The study aimed to investigate and describe the pollen morphology of six nectariferous and polleniferous members of family fabaceae by using light and scanning electron microscope. Pollen grains of Albizia lebbeck, Bauhinia variegata, Caesalpinia decalpetala, Cassia fistula, Dalbergia sissoo and Robinia pseudoacacia were examined for the morphological characterization. The pollen grains were analysed in terms of aggregation, shape, shape class, size, aperture, polarity, symmetry, surface pattern and exine comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…However, variation of pollen exine ornamentation can be used as a reference to evaluate the degree of plant evolution and species diversity in Fabaceae (Zhang & Dai, 2022). Scanning and observing the exine ornamentation of pollen grains by high-resolution SEM can be used as a basis for identifying legume pollen and evaluating species diversity in future studies (Jamwal et al, 2021;Oliveira, Restrepo, Santos, Queiroz, & Santos, 2022)…”
Section: Exine Ornamentationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, variation of pollen exine ornamentation can be used as a reference to evaluate the degree of plant evolution and species diversity in Fabaceae (Zhang & Dai, 2022). Scanning and observing the exine ornamentation of pollen grains by high-resolution SEM can be used as a basis for identifying legume pollen and evaluating species diversity in future studies (Jamwal et al, 2021;Oliveira, Restrepo, Santos, Queiroz, & Santos, 2022)…”
Section: Exine Ornamentationmentioning
confidence: 99%
“…The morphology of pollen gains is controlled by the genotype of the species, with strong genetic conservation and a lot of evolutionary information (Doyle, 1969;Erdtman, 1952;Martin, 1978;Solomon, 1983;Walker, 1974). Numerous studies have suggested that pollen morphology could provide evidence for plant taxonomy and evolution (Atasagun, Aksoy, & Martin, 2018;Bahadur, Taj, Long, & Hanif, 2022;El Kholy, Mohamed, & Khafagi, 2023;Jamwal et al, 2021;Khan et al, 2022). Palynological analyses have been sporadically performed in Fabaceae at a range of different taxonomic levels, such as in the Astragalus sect.…”
mentioning
confidence: 99%